Trends and patterns of private investment in India - Jagannath, Mallick (Bangalore, 2009)
This study aims at providing an understanding of the economic structure and structural changes in private investment in the Indian economy. The overarching problem addressed in this study is whether or not identifiable structural transformation has occurred due to economic reforms in India. What were the trends in private investment in India? Structural transformation is confined to the shifting or movement of resources from one sector to another within the private economy. This study utilised descriptive statistics like annual average growth rate, share and Z test statistics to find out the sectoral and sub-sectoral contributions to the growth of private investment in India as well as to verify the structural changes. The research questions addressed were: What were the short term and long term trends in private investment at the aggregate, sectoral and sub-sectoral levels? What was the contribution of the sectors and their sub-sectors to the growth of private investment in India before and after the reforms? Did an identifiable structural transformation occur in the Indian economy? The National Accounts Statistics (NAS) was used for the data on private investment for the analysis of this study. The analysis revealed that the rate of capital formation had increased in the private sector and decreased in the public sector after economic reforms. Further, the industrial sector had been ranked one in terms of its contribution to the growth of private investment followed by the service and agricultural sectors in India in the short term as well as long term. However, the growth of private investment in the service sector was considerably higher in the post reform period than the pre-reform period. Further, the annual average of growth of private investment in the service sector was almost equal to the industrial secto in the post-reform period. Therefore, the service sector played a very important role in attracting private investment during the economic reforms period. The service sector comprises, among others, consumer and producer services. Further, it was found that the contribution of producer services, which includes real estate, ownership of dwellings and business services, and others, contributed to the growth of private investment in the service sector in India. In this context it is very important to study whether or not identifiable structural transformations in terms of private investment occurred in India.
Keywords: Indian Economy; Private Investment - patterns and trends